Solar-driven alkaline water electrolysis with multifunctional catalysts - Sun, Zixu (2020)
Alkaline water electrolysis (AWE) holds great promise for a truly sustainable energy future if it can be driven by renewable energy sources such as solar and wind. The main challenge arises from the serious partial loading issue when intermittent and unstable renewable energy is coupled to water electrolyzers. An energy storage device can mitigate this incompatibility between water electrolyzer and renewable energy sources. Herein, an AWE device driven by solar photovoltaic (PV) through a full cell of lithium-ion battery (LIB) as an energy reservoir is demonstrated (PV−LIB−AWE). Stable power output from LIB drives the water electrolyzer for steady hydrogen production, and thus overcomes the partial loading issue of AWE. Moreover, a multifunctional hierarchical material, porous nickel oxide decorated nitrogen-doped carbon (NC) support, with excellent electrochemical performances for LIBs, oxygen evolution reaction (OER), and hydrogen evolution reaction (HER) for the PV−LIB−AWE system is developed. Density functional theory calculations show that the strong interaction between metal oxide and NC tailors the electronic structure and then optimizes activation energy of OER process. PV−LIB−AWE integrated system demonstrated here offers an alternative approach to drive water electrolysis with intermittent renewable energy for a truly sustainable energy future.